Water distribution and textual properties of heat-induced pork myofibrillar protein gel as affected by sarcoplasmic protein. (April 2019) - Xia, Minquan; Chen, Yinxia; Guo, Juanjuan; Huang, Han; Wang, Lan; Wu, Wenjin; Xiong, Guangquan; Sun, Weiqing
Abstract: This study investigated the effects of sarcoplasmic protein (SP) on myofibrillar protein (MP) gel properties by adding different concentrations of SP (0, 10, 20 and 30 g/100 g) into MP, with both of them isolated from pork. The interaction between MP and SP and the potential mechanism were also explored. When compared with the untreated MP, adding 20 g/100 g SP showed the maximum water-holding capacity, with an increase of 31.74%, as well as the most compact and densest MP gel network as indicated by the scanning electron microscopy. SP addition could also increase the binding water capacity of the gel due to shorter T22 and less free water. Furthermore, adding 20 g/100 g SP increased the values of springiness, hardness and chewiness from 0.35 to 0.70, 142.86 to 581.63, and 11.88 to 92.55, while adding 10 g/100 g SP increased the cohesiveness value from 0.17 to 0.25. These results indicated that moderate SP addition can improve the gel properties of MP. Highlights: Sarcoplasmic protein (SP) notably affects myofibrillar protein (MP) gel property. 20% SP addition largely improves MP gel texture property and water-holding capacity. SEM showed the most compact and dense MP gel network by 20% SP addition. Moderate SP could improve MP gel texture and WHC by padding the network and increasing the hydration.